2017
DOI: 10.1016/j.nbd.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deletion increases hippocampal granule cell excitability in male and female mice

Abstract: Deletion of the mTOR pathway inhibitor PTEN from postnatally-generated hippocampal dentate granule cells causes epilepsy. Here, we conducted field potential, whole cell recording and single cell morphology studies to begin to elucidate the mechanisms by which granule cell-specific PTEN-loss produces disease. Cells from both male and female mice were recorded to identify sex-specific effects. PTEN knockout granule cells showed altered intrinsic excitability, evident as a tendency to fire in bursts. PTEN knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 78 publications
(112 reference statements)
3
38
0
Order By: Relevance
“…On the other hand, increased soma area was associated with decreases in R n in hippocampal neurons from mice (Santos et al . ), as well as in motoneurons from the oculomotor nucleus of rats (Torres‐Torrelo et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, increased soma area was associated with decreases in R n in hippocampal neurons from mice (Santos et al . ), as well as in motoneurons from the oculomotor nucleus of rats (Torres‐Torrelo et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In pyramidal cells, for example, dendritic hypercomplexity is associated with altered neuronal activity as a result of a reduction in spike frequency adaptation episodes (van der Velden et al 2012). On the other hand, increased soma area was associated with decreases in R n in hippocampal neurons from mice (Santos et al 2017), as well as in motoneurons from the oculomotor nucleus of rats (Torres-Torrelo et al 2014). In the present study, we observed that SH increases the morphological complexity and somatic surface area and also decreases the R n of tonically active RA motoneurons.…”
Section: Hypoxia Induces Morphological Changes In Tonically Active Ramentioning
confidence: 91%
“…PTEN-ASD subjects and mice often develop (or are prone to) seizures, a condition of synchronized pathological firing, and it is accepted that neuronal hyperexcitability is a driving force for epileptogenesis. Aberrant circuitry of the dentate gyrus because of ectopic migration, hypertrophy, and hyperexcitability has been shown to result in increased spontaneous EPSCs, fewer iPSCs, and multiple population spikes and is also a wellknown factor for temporal lobe epilepsy (Nadler 2003;Pun et al 2012;LaSarge et al 2016;Santos et al 2017). From a molecular point of view, an involvement of potassium channels in hippocampal hyperexcitability of 8-week-old Pten f/f ; Gfap-cre mice has been implicated (Lugo et al 2014;Nguyen and Anderson 2018).…”
Section: Pten In Connectivity and Ltp/ltdmentioning
confidence: 99%
“…Deletion of PTEN from 2- to 4-week-old mice produces epilepsy in Nestin- and Gli1-Cre lines ( 88 , 89 ). PTEN deletion leads to granule cell mossy fiber axon abnormalities, with evidence for increased axon collateralization in the hilus and stratum lucidum ( 91 ) and the development of recurrent excitation in acute hippocampal slices ( 92 , 93 ). Epilepsy can develop in these animals, however, without robust mossy fiber sprouting ( 89 ).…”
Section: Regulation Of Mossy Fiber Sprouting By Mtormentioning
confidence: 99%